PENGARUH MOTIVASI DAN TEKNOLOGI INFORMASI TERHADAP KINERJA KARYAWAN DI BADAN PUSAT STATISTIK (BPS) KABUPATEN BOGOR DENGAN PRODUKTIVITAS KERJA SEBAGAI VARIABEL INTERVENING - Purnama Indah, Dwi; Widyastuti, Tri; Salim , Fahruddin (EKOBISMAN : JURNAL EKONOMI BISNIS MANAJEMEN, 2021)
The purpose of this study was to determine the effect of motivation and information technology on employee performance through work productivity as an intervening variable. The population of this study are employees or female employees who work at the Central Bureau of Statistics, Bogor Regency. The number of polls was 62 peopls. The statistical method used in this study is the Patrial Least Square (PLS) or Structural Equation Modeling (SEM) equation which is operated through the smartPLS program. In this study, it can be seen that motivation and information technology have a positive and significant effect on employee performance and work productivity also have a positive and significant effect on employee performance.